A valuable MRI examination method for prostate cancer screening. Issue 48 (25th November 2020) - Yang, Xuezhen; Shan, Lianqiang; Cao, Haiming; Jiang, Xu; Ma, Xueping
Abstract : Abstract: To investigate the value of the 1.5T magnetic resonance imaging (MRI) apparent diffusion coefficient (ADC) and the prostate imaging reporting and data system (PI-RADS) score in prostate cancer (PCa) screening. Forty PCa patients diagnosed by pathology from December 2014 to September 2018 were recruited as the PCa group; 60 patients with benign prostatic hyperplasia (BPH) were recruited as the benign group. Patients from both groups underwent 1.5T MRI scanning. The prostate ADC values, exponential apparent diffusion coefficient (eADC) values, and PI-RADS scores of patients from the 2 groups were compared. The different methods for PCa diagnosis were compared. The ADC values of patients in the PCa group were significantly lower than those in the benign group, whereas the eADC values of patients were significantly higher than those in the benign group, with statistically significant differences ( P  < .05). The differences in the PI-RADS scores of patients from the 2 groups were statistically significant ( P  < .05). Receiver Operating Characteristic (ROC) curve results showed that the ADC value combined with the PI-RADS score was superior to the ADC value or the PI-RADS score alone in sensitivity, specificity, and Youden index for PCa diagnosis. By comparing the area under the curve (AUC) of each ROC curve from the different diagnostic methods, the combination of ADC value and PI-RADS score showed the largest area. The ADC value from 1.5T MRI combined with the PI-RADS score could be used as the standard for PCa screening, which would effectively improve screening for PCa and be valuable for clinical applications.